Language Anxiety for Students of Intermediate Speaking Proficiency Level - Akhmad, Enni; Aba, La; R Saleh, Yuwin (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The focus of research on students' anxiety when speaking a foreign language, such as English, has shifted to language learning and education. However, the experience of students who reached the intermediate level remains underexplored, particularly in the context of students in intermediate speaking classes. This study aims to identify the students’ reasons for feeling anxious and whether intermediate students also experience language anxiety. This qualitative research involved 20 participants from an intermediate-speaking class of fifth-year English Education Department undergraduate students at IAIN Sultan Amai Gorontalo. Data were collected using an unstructured interview and an observation sheet. Triangulation was used to analyze data by checking the credibility of data from interviews and observations. According to the findings of this study, students were anxious for three reasons: they were afraid of making mistakes, they were shy to speak, and they had lost motivation to speak. The students who joined the intermediate speaking class experienced anxiety as their psychological disorder. Anxiety was identified as the dominant psychological disorder among the students. It supported the previous research that found students of all levels experienced anxiety in their speaking English class. As a result, to alleviate students' anxiety about speaking a foreign language, teachers must consider the students' anxiety when developing teaching materials and media.